Optimalisasi Aktivitas Dan Hasil Belajar Peserta Didik Pada Mapel Bahasa Indonesia Menulis Teks Negosiasi Melalui Model Project Based Learning Metode Demonstrasi Pada Kelas X IIS Man 3 Payakumbuh Semester Genap T.P. 2021/2022 - Shaif Abdul Hadi (Departement of Mathematics Education, 2022)
The purpose of this Classroom Action Research was to improve Indonesian language learning outcomes on the subject of Writing Negotiated Texts for students in class X IIS in the academic year 2021/20122 using the Project Based Learning model. This research was conducted for 20 weeks from January to May 2022 (9 meetings) with two cycle methods, namely cycle I knowledge and cycle I skills as well as cycle II. The first cycle of knowledge consists of three meetings, the third meeting is daily test, cycle I knowledge, daily test skills and cycle II for knowledge and skills consists of planning, action, observation, and reflection. The subjects of this study were students of class X IIS even semester of MAN 3 Payakumbuh Academic Year 2021/2022. The data collection technique is by holding daily exams for each cycle as a result of student learning. The results obtained from this study are participatory discussions can increase students' activities and learning outcomes. This is evident from the results obtained in Cycle I 62% for the activeness of students in the second cycle rose to 83% for learning activities or an increase of 21%. In Cycle I, the percentage of knowledge of student learning outcomes from 64% to 82% in Cycle II or an increase of 18% for Knowledge learning outcomes and in Cycle I Skills, the percentage of student learning outcomes from 63% to 77% in Cycle II or an increase 14% for Skills learning outcomes. The conclusion of this research is that learning using the Scientific method of Project Based Learning learning model can improve student learning outcomes so that fellow teachers can make reference to vary the learning methods implemented in schools